After Auschwitz : the difficult legacies of the GDR - Heitzer, Enrico 1977- HerausgeberIn; Jander, Martin 1955- HerausgeberIn; Kahane, Anetta 1954- HerausgeberIn; Poutrus, Patrice G. 1961- HerausgeberIn (Berghahn, 2021)
"From the moment of its inception, the East German state sought to cast itself as a clean break from the horrors of National Socialism. Nonetheless, the precipitous rise of xenophobic, far-right parties across the present-day German East is only the latest evidence that the GDR's legacy cannot be understood in isolation from the Nazi era nor the political upheavals of today. This provocative collection reflects on the heretofore ignored or repressed aspects of German mainstream society-including right-wing extremism, anti-Semitism and racism-to call for an ambitious renewal of historical research and political education to place East Germany in its proper historical context"--